Cardiovascular and cerebrovascular risk markers in Parkinson's disease: Results from a case−control study. (16th June 2021) - Alves, Mariana; Pita Lobo, Patrícia; Kauppila, Linda Azevedo; Rebordão, Leonor; Cruz, M. Manuela; Soares, Fátima; Cruz, João; Tornada, Ana; Caldeira, Daniel; Reimão, Sofia; Oliveira, Victor; Ferro, José M.; et al.
Abstract: Background: The relationship between Parkinson's disease (PD) and cardiovascular and cerebrovascular disease is not yet well established. Recent data suggest an increased risk of myocardial infarction and stroke in PD patients. Therefore, we designed a study to assess surrogate markers of cardiovascular and cerebrovascular risk in PD. Methods: We conducted a case−control study comparing PD patients recruited from a Movement Disorders Unit with controls randomly invited from a primary healthcare center. All participants underwent a detailed clinical evaluation, including medical history, physical assessment, carotid ultrasound, blood and urine analysis, and 24‐h ambulatory blood pressure monitoring. The primary outcome was the carotid intima‐media thickness (CIMT). Results: We included 102 participants in each study arm. No significant difference was found in the CIMT among groups (MD: 0.01, 95% CI: −0.02, 0.04). Carotid plaques were more frequent in PD patients (OR: 1.90, 95% CI: 1.02, 3.55), although the lipid profile was more favorable in this group (LDL MD: −18.75; 95% CI: −10.69, −26.81). Nocturnal systolic blood pressure was significantly higher in PD patients (MD: 4.37, 95% CI: 0.27, 8.47) and more than half of the PD patients were non‐dippers or reverse dippers (OR: 1.83, 95% CI: 1.04, 3.20). Conclusion: We did not find a difference in CIMT between PD and controls. A higher frequency of carotid plaques and abnormal dipper profile supports the hypothesis that PD patients are not protected from cardiovascular and cerebrovascular disease. Abstract :